2000
DOI: 10.1128/mcb.20.17.6466-6475.2000
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamic Properties of a Glucocorticoid Receptor-Induced Chromatin Transition

Abstract: Activation of the mouse mammary tumor virus (MMTV) promoter by the glucocorticoid receptor (GR) is18:3633-3644). We have reconstituted MMTV LTR DNA into a polynucleosome array using Drosophila embryo extracts. We show binding of purified GR to specific GR elements within a large, multinucleosome array and describe a GR-induced nucleoprotein transition that is dependent on ATP and a HeLa nuclear extract. Previously uncharacterized GR binding sites in the upstream C nucleosome region are involved in the extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 55 publications
(62 reference statements)
1
69
0
Order By: Relevance
“…Their joint action allows for the binding to DNA of a transcriptional activator (NF-1) whose binding site was previously occluded by a translationally positioned nucleosome (Archer et al, 1992), and transcription begins. An additional attractive parallel between HO and the MMTV LTR is in the transient liaison that the activator has with its target promoter: Swi5p leaves the DNA in 5 min (Cosma et al, 1999), and GR shuttles on and o DNA on a timescale of seconds (McNally et al, 2000) ± an interesting possibility with some experimental support (Fletcher et al, 2000) is that the remodeling action of SWI/SNF displaces from the DNA the very activator that targets it (Urnov and Wol e, 2001). …”
Section: Ho Endonuclease Gene Activation: Mating As Serious Businessmentioning
confidence: 99%
“…Their joint action allows for the binding to DNA of a transcriptional activator (NF-1) whose binding site was previously occluded by a translationally positioned nucleosome (Archer et al, 1992), and transcription begins. An additional attractive parallel between HO and the MMTV LTR is in the transient liaison that the activator has with its target promoter: Swi5p leaves the DNA in 5 min (Cosma et al, 1999), and GR shuttles on and o DNA on a timescale of seconds (McNally et al, 2000) ± an interesting possibility with some experimental support (Fletcher et al, 2000) is that the remodeling action of SWI/SNF displaces from the DNA the very activator that targets it (Urnov and Wol e, 2001). …”
Section: Ho Endonuclease Gene Activation: Mating As Serious Businessmentioning
confidence: 99%
“…The GR has been shown in vitro to stimulate BRG1 chromatin remodeling using partially puri®ed complexes from either HeLa cells or from rat liver tissue (Ostlund Farrants et al, 1997). On MMTV LTR DNA reconstituted into polynucleosome arrays with Drosophila embryo extracts, puri®ed GR required ATP and HeLa nuclear extract to induce chromatin remodeling (Fletcher et al, 2000). Yeast Swi/Snf stimulated transcription via the N-terminal transactivation domain of the GR, tl, from assembled chromatin templates (Wallberg et al, 2000).…”
Section: Gr and Chromatin-remodeling Complexesmentioning
confidence: 99%
“…The latter scenario has precedent in other nuclear receptor studies. Glucocorticoid receptor-mediated remodeling of a reconstituted mouse mammary tumor virus nucleosomal array has been shown to require ATP and remodeling factors, as well as interaction with acetyltransferase coactivators, supporting the idea of distinct requirements for each of these two remodeling mechanisms (10,11). The estrogen and retinoic acid receptors also have been shown to require ATP-dependent remodeling complexes in the chromatin context (49,50).…”
Section: Discussionmentioning
confidence: 87%
“…The role of ATP-dependent mechanisms such as SWI/SNF, Mi2/NURD, and ISWI (5) in nuclear receptor-mediated regulation has also been demonstrated. Studies using the glucocorticoid receptor on the mouse mammary tumor virus promoter, which has been shown to have positioned nucleosomes (6), have demonstrated a requirement for SWI-SNF complexes and their ligand-induced targeting to the promoter to activate gene expression (7)(8)(9)(10)(11). More recently, it has been demonstrated that glucocorticoid receptor activation induces nucleosome translational positioning on the mouse mammary tumor virus promoter (12).…”
mentioning
confidence: 99%